A novel low-voltage low-power bulk-driven cascade current mirror - Li Yani; Yang Yintang; Zhu Zhangming (2010 3rd International Conference on Advanced Computer Theory and Engineering(ICACTE), 2010)
A novel low-voltage low-power PMOS cascade current mirror employing the bulk-driven technique is described in this paper. Based on SMIC 0.18μm CMOS process, the characteristics of the low-voltage bulk-driven cascade current mirror are analyzed and validated, including the input/output resistance, the system dc transmission error, the frequency characteristics and noise performance, etc. The simulation results reveal that: this bulk-driven cascade current mirror is able to reduce the input voltage drop to 0.3V, and it has the better current driving ability than the gate-driven cascade current mirror does under the same conditions, along with the same good current following characteristic as the gate-driven cascade current mirror. The bulk-driven cascade current mirror achieves the low-voltage low-power characteristic at the cost of the linearity of output current vs input voltage and frequency bandwidth, as well as noise performance. The presented low-voltage bulk-driven cascade current mirror has a good performance for low-frequency low-voltage applications in the design of CMOS analog integrated circuits.